„Carmen de triumpho Christi” Macaria Muzia (‘Carmen de Triumpho Christi’ by Macario Muzio) - Górka, Elżbieta (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2024)
This article presents one of the most famous Renaissance Latin epyllions dealing with the motif of the Harrowing of Hell – Carmen de Triumpho Christi by Macario Muzio (a. 1440–a. 1523), a nobleman from Camerino. Written at the end of the 15th century, the work gained popularity and was eagerly imitated by other humanists (including Erasmus of Rotterdam and Eobanus Hessus). The epyllion, constructed according to the rules of ancient epic, is an example of the Christianisation of classical genres in the Renaissance. The article presents the life of the author and his views on Christian poetry, as well as a thorough analysis of the work. It provides the Latin text of Carmen, accompanied by similia, and its Polish translation, supplemented by a commentary.